Gelatin MAGIC powder as nutrient-delivering 3D spacer for growing cell sheets into cost-effective cultured meat. (November 2021) - Park, Sohyeon; Jung, Sungwon; Choi, Moonhyun; Lee, Milae; Choi, Bumgyu; Koh, Won-Gun; Lee, Sangmin; Hong, Jinkee
Abstract: Cell cultured meat is artificial meat obtained by culturing animal-derived cells in vitro, and received significant attention as an emerging future protein source. The mass proliferation of cells in the cultured meat production is a strenuous process that delays the commercialization of cultured meat because it requires an expensive culture medium for a long period. Herein, we report on a strategy to develop advanced cultured meat using fish gelatin mass growth-inducing culture (MAGIC) powder and myoblast sheets. The MAGIC powder had an edible gelatin microsphere (GMS) structure and exhibited different morphologies and bonding activities depending on the degree of crosslinking. We analyzed the loading and release of nutrients for each GMS with diverse surface properties, and selected the most effective GMSs to improve the proliferation of myoblasts under serum-reduced medium. The GMSs exerted four significant functions in the culture of myoblast sheets, and consequently produced cost- and time-effective meat-like cell sheets than the conventional method. We prepared cultured meats composed of cell sheet containing GMSs and evaluated the quality of the cultured meat by comparing the tissue properties with soy meat and chicken breast.